Labor Education Curriculum Design and Practice from an Interdisciplinary Perspective - Xu, Xiaoling; Zuo, Hang (Journal of Educational Theory and Practice, 2026)
The effective implementation of labor education in the new era urgently needs to break through the barriers of single disciplines and overcome practical difficulties such as "skill-oriented" and "formalistic" approaches. This paper takes the practical and spiritual attributes of labor education as its logical starting point, defines the core connotation of interdisciplinary labor education courses, and constructs a four-in-one curriculum framework of "goals-content-implementation-evaluation." Using the interdisciplinary project "Rainwater Garden Chili Pepper Planting" as a case study, research shows that interdisciplinary labor education courses can effectively achieve the collaborative educational goals of "cultivating morality through labor, enhancing intelligence through labor, improving physical health through labor, and fostering aesthetic appreciation through labor."